PENERAPAN DIGITAL MARKETING MELALUI SOCIAL MEDIA PADA UMKM (USAHA MIKRO KECIL DAN MENENGAH) UD.VIRA JEMBER - Anggie Priscelia; Pudjo Suharso; Hety Mustika Ani (JPEKBM (Jurnal Pendidikan Ekonomi, Kewirausahaan, Bisnis dan Manajemen), 2023)
The purpose of this research is describe the application of digital marketing through social media on UD. Vira Jember with a qualitative approach. Data collection methods used are interviews, observation and documentation. Data analysis methods used are domain analysis and taxonomic analysis. The results show that UD.Vira applies digital marketing in its marketing through social media platforms Instagram and WhatsApp. UD.Vira uses the "4C concept" consisting of context, communication, collaboration and connection. Based on the 4 concepts applied, communication and connection have not been implemented optimally. For example, UD. Vira has not provided complete information regarding the price of product in every post on social media. As for the connection concept, UD.Vira has less attention to product ratings from consumers. Based on this research, the conclusion that UD. Vira is able to carry out the sales concept but is not maximal to apply the 4 concepts correctly.